Recent advances in the biosynthetic mechanisms, regulation, and detoxification strategies of deoxynivalenol in Fusarium graminearum - He, Mingfang; Lei, Yaping; Yan, Haiyuan; Sun, Chao; Gu, Xiaolong (Frontiers in Nutrition, 2025)
Fusarium graminearum, the major causal agent of Fusarium head blight (FHB), produces the trichothecene mycotoxin deoxynivalenol (DON), which threatens food and feed safety worldwide. This review synthesizes recent advances in DON biosynthesis, emphasizing the TRI gene cluster and its pathway enzymes, transcriptional regulators, and signaling cascades. In parallel, it provides a comprehensive analysis of the molecular mechanisms involved in regulating DON biosynthesis, with a focus on the TRI cluster. In additionally, current progress in detoxification strategies is summarized, covering physical, chemical, and biological methods aimed at mitigating DON contamination in food and feed. This review further explores the endogenous environmental factors influencing DON synthesis and offering insights to the development of integrated control strategies against DON contamination. By integrating the current findings, this review aims to support the development of effective strategies, control F. graminearum and mitigate FHB.